Long swings and chaos in the exchange rate in a DSGE model with a Taylor rule - Mikael Bask (Bank of Finland, 2007)
A DSGE model with a Taylor rule is augmented with an evolutionary switching between technical and fundamental analyses in currency trade, where the fractions of these trading tools are determined within the model. Then, a shock hits the economy. As a result, chaotic dynamics and long swings may occur in the exchange rate, which are appealing features of the model given existing empirical evidence on chaos and long swings in exchange rate fluctuations.
URN:NBN:fi:bof-20140807432
Keywords: C65; E32; E44; E52; F31; 330; chaotic dynamics; foreign exchange; fundamental analysis; monetary policy; technical analysis